Hubungan Pengetahuan, Sikap Dan Dukungan Keluarga Terhadap Perilaku Kepatuhan Mengkonsumsi Tablet Zat Besi (Fe) Pada Ibu Nifas: Relationship of Knowledge, Attitudes and Family Support to Compliance Behavior of Consuming Iron (Fe) Tablets in Postpartum Mothers - Mulyani, Sindi Sri (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: The Maternal Mortality Rate (MMR) is still quite high, namely 359 deaths per 100,000 live births, according to the 2018 Indonesian Demographic Health Survey (IDHS). The most common reason for maternal death during the post-pregnancy period is fatigue after 28% of pregnancy; 24% eclampsia; 11% illness; 9% lack of energy after delivery; 5% premature termination; 5% delay in work; 3% embolism; 3% weakness; and different causes 22%. One of them can be LBW because the mother has anemia, and one of them can be anemia because the mother does not take iron (Fe) tablets. Methods: The purpose of this report is to determine the relationship between knowledge, attitudes, and family support on adherence to the consumption of iron (Fe) tablets at PMB Mrs. Y. This research uses descriptive analytics with a cross-sectional approach. The population of this study was 52 postpartum mothers and the sampling technique used was simple random sampling with a sample of 34 postpartum mothers. Results: The results of this study indicate that there is a significant relationship between knowledge and compliance behavior with a p-value of 0,012; attitudes and compliance behavior with a p-value of 0,047; and family support with compliance behavior with a p-value of 0,016. Discussion: The suggestion from this study is that postpartum mothers add more knowledge, especially regarding adherence to consuming iron tablets and anemia in postpartum mothers and it can be concluded that there is a relationship between knowledge, attitudes, family support, and behavior of consuming Fe tablets at PMB Mrs. Y Mekarwangi Village, Haurwangi District, Cianjur Regency in 2022.